Central mechanisms mediating the hypophagic effects of oleoylethanolamide and N-acylphosphatidylethanolamines: different lipid signals? - Romano, Adele; Tempesta, Bianca; Provensi, Gustavo; Passani, Maria B.; Gaetani, Silvana (Frontiers in Pharmacology, 2015)
The spread of ‘obesity epidemic’ and the poor efficacy of many anti-obesity therapies in the long-term highlight the need to develop novel efficacious therapy. This necessity stimulates a large research effort to find novel mechanisms controlling feeding and energy balance. Among these mechanisms a great deal of attention has been attracted by a family of phospholipid-derived signaling molecules that play an important role in the regulation of food-intake. They include N-acylethanolamines (NAEs) and N-acylphosphatidylethanolamines (NAPEs). NAPEs have been considered for a long time simply as phospholipid precursors of the lipid mediator NAEs, but increasing body of evidence suggest a role in many physiological processes including the regulation of feeding behavior. Several observations demonstrated that among NAEs, oleoylethanolamide (OEA) acts as a satiety signal, which is generated in the intestine, upon the ingestion of fat, and signals to the central nervous system. At this level different neuronal pathways, including oxytocinergic, noradrenergic, and histaminergic neurons, seem to mediate its hypophagic action. Similarly to NAEs, NAPEs (with particular reference to the N16:0 species) levels were shown to be regulated by the fed state and this finding was initially interpreted as fluctuations of NAE precursors. However, the observation that exogenously administered NAPEs are able to inhibit food intake, not only in normal rats and mice but also in mice lacking the enzyme that converts NAPEs into NAEs, supported the hypothesis of a role of NAPE in the regulation of feeding behavior. Indirect observations suggest that the hypophagic action of NAPEs might involve central mechanisms, although the molecular target remains unknown. The present paper reviews the role that OEA and NAPEs play in the mechanisms that control food intake, further supporting this group of phospholipids as optimal candidate for the development of novel anti-obesity treatments.